ANALISIS LAPORAN REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH UNTUK MENGUKUR KINERJA KEUANGAN PADA PEMERINTAH KABUPATEN MUSI BANYUASIN - Irfansyah, Ahmad (Institut Rahmaniyah Sekayu, 2025)
This research is a process of assessing the level of progress in the implementation of regional finance, specifically measuring the financial performance of the Regional Revenue and Expenditure Budget at the Musi Banyuasin Regency Government office. The ratios used in measuring financial performance are the effectiveness ratio and efficiency ratio based on the effectiveness ratio from 2021-2023 with an average of 97.52% with effective criteria. This indicates that the realization of Regional Original Revenue does not exceed the Regional Original Revenue budget and is almost close to 100%. However, the difference between the budget and the realization of this revenue can cause an imbalance in regional financial management. Meanwhile, based on the efficiency ratio, it is in the less efficient category because it is in the range of 90-100%, meaning the amount of realized expenditure is not higher than the budget. This indicates that there are challenges in budget control that are not fully planned or implemented.